Assessment of nutrition status of chronic kidney disease patients “on dialysis” and “not on dialysis”: a diet-based analysis - Verma, Shailvi; Sonkar, Satyendra Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Nutritional status and micronutrient levels of CKD patients are very critical aspects of their overall health. CKD patients with T2DM face additional challenges in managing their nutritional status. This is because of the correlation between T2DM-related dietary considerations and CKD. CKD patients with T2DM require management of both conditions simultaneously. This needs a careful balance of dietary restrictions and recommendations. Thus, the focus of present research was to assess nutrition status of CKD patients suffering with T2DM on dialysis and not on dialysis. Methods: Total 80 patients were considered in this research, 40 patients of T2DM related CKD on dialysis and 40 patients of T2DM related CKD not on dialysis. Central tendency tests have been conducted here. Results: For T2DM CKD patients not on dialysis, vegetarians consumed maximum water followed by eggetarian. Non vegetarians consumed minimum water in comparison to other two. Maximum vegetarians don’t have hypertension, all eggetarians have hypertension, and more than half non vegetarians have hypertension. All vegetarians were males, more than half females were non vegetarians, equal number of males and females were eggetarian. Conclusions: The type of diet that is vegetarian, non-vegetarian or eggetarian also decides the type and quantity of nutrition being consumed. Thus it is critical to assess the nutrition based on diet type for T2DM CKD patients on dialysis and not on dialysis.